Economic Growth, Carbon Dioxide Emissions, Renewable Energy and Globalization - LeitÃ£o, Nuno Carlos (International Journal of Energy Economics and Policy, 2014)
This article investigates the correlation between economic growth, carbon dioxide emissions, renewable energy and globalization for the period 1970-2010, using time series (OLS, GMM, unit root test, VEC model, and Granger causality) to Portuguese economy. OLS estimator and GMM model demonstrate that carbon dioxide emissions and renewable energy are positively correlated with economic growth. The econometric models also show that the overall index of globalization has a positive effect on growth. The Granger causality reports a unidirectional causality between renewable energy and economic growth. Keywords: Economic growth; renewable energy; globalization. JEL Classifications: C13; F10; Q20